Nursing Intervention for the Burden of Family Caregiver Patient with Lung Cancer: Scoping Review - Hesti Platini; Indra Maulana (GLOBAL HEALTH SCIENCE GROUP, 2024)
Cancer sufferers during treatment, and cancer survival have a big influence on the family members around them. This scoping review is part of the development of a support model for family members of people diagnosed with lung cancer. Objective:o identify nursing support for caregiver burden in family caregivers of cancer patients. This scoping review was guided PRISMA Scr six-stage scoping review framework. All available published articles from January 2020 to the beginning of 2024 were systematically searched through the PubMed, CINAHL, EBSCO, and Science Direct databases. Each key journal is searched manually. Overall, 402 articles were screened, and 16 articles were ultimately included. The results of the analysis were found to be 6 components of nursing support: psychological and educational support, psychological and educational support mainly Information and Communication Technology, attention to support, support aimed at reducing caregiver stress, support for patients and caregivers, etc. Of the 32 studies, 6 were randomized controlled trials (RCTs), and the remaining 10 were non-RCTs. The results of the scoping review categorize nursing support for caregiver burden in family caregivers of cancer patients into 6 components. Future research should be more specific regarding cancer.